1996
DOI: 10.1097/00004714-199610000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clozapine on Plasma Cytokine and Soluble Cytokine Receptor Levels

Abstract: The antipsychotic drug clozapine frequently induces fever during the first weeks of administration. In addition, it has been shown that clozapine increases plasma soluble interleukin-2 receptor (sIL-2r) levels as early as 1 week after treatment is started. These findings suggest that clozapine has immunomodulatory effects. To investigate this issue in more detail, we assessed the time course of rectal temperature, blood cell counts, and cytokine and soluble cytokine receptor plasma levels during 6 weeks of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
121
1
5

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(131 citation statements)
references
References 38 publications
4
121
1
5
Order By: Relevance
“…It was reported that the plasma levels of sIL-2r and TNF-␣ were significantly increased by clozapine treatment per se; whereas, IL-6 levels were only increased during clozapine-induced fever (Maes et al 1994;Pollmächer et al 1995Pollmächer et al , 1996. At first glance, these results do not seem to be compatible with our in vitro results.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…It was reported that the plasma levels of sIL-2r and TNF-␣ were significantly increased by clozapine treatment per se; whereas, IL-6 levels were only increased during clozapine-induced fever (Maes et al 1994;Pollmächer et al 1995Pollmächer et al , 1996. At first glance, these results do not seem to be compatible with our in vitro results.…”
Section: Discussioncontrasting
confidence: 93%
“…Independent of such side effects, clozapine treatment consistently increases the plasma levels of cytokines and soluble cytokine receptors that are pivotal immune mediators. In particular, there are consistent reports on increases in the plasma levels of tumor necrosis factor-␣ (TNF-␣ ), soluble TNF-receptor p55 (TNF-Rp55), TNF-Rp75 and soluble interleukin-2 receptor (Maes et al 1994;Pollmächer et al 1995;Pollmächer et al 1996). These effects were already evident after the first week of treatment and persisted for at least 6 weeks .…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Among them, tumor necrosis factor-a (TNF-a), which can be secreted by astrocytes, is a strong repressor of GLT-1 expression (Su et al, 2003). Interestingly, clozapine raises the plasma levels of TNF-and soluble TNF receptors p55 and p75 in schizophrenic patients (Pollmä cher et al, 1996). Alternatively, the action of clozapine on GLT-1 expression may be the consequence of the blockade of neurotransmitter receptors, such as dopamine and serotonin receptors (Stahl, 1999), which are expressed in astrocytes (Bal et al, 1994;Maxishima et al, 2001).…”
mentioning
confidence: 99%
“…Some studies reported that short-term treatment with clozapine may induce the production of pro-inflammatory cytokines such as IL-6, INF␥ and TNF␣, an effect that tends to disappear upon prolonged treatment. 22,23 Moreover, dysregulation in cytokines production (IL-1, IL-6 and TNF) has also been described in patients with major depressive disorders, Alzheimer's disease, panic disorder, obsessive-compulsive disorder, autism and stress-induced anxiety. [24][25][26][27][28][29] This lack of specificity and the possible biasing influence of the above-mentioned factors weaken the relevance of serum/plasma-based investigations on immune system abnormalities in schizophrenic patients.…”
mentioning
confidence: 99%